THE LANGUAGE Of NEGATION IN NYÄYA - Vattamky, John (Journal of Dharma, 1981)
Traditionally, in many nyãya authors, the topic of negation is treated along with the subject of absence. Absence itself, in nyãya treatment of it, involves the following questions : (a) Is non-perception (anupalabdhi) to be considered a separate means of valid cognition? (b) Is absence itself to be accepted as a separate category ? (c) How is absence to be cognized? (d) Finally, how many kinds of absences are there? Though not treated in nyãya wo,-ks as a separate topic, we can include such questions as the following also in treating absence and negation : (a) What role did the concepts of absence and negation play in the formulation of the nyãya ideas on souls and their liberation (mukti)? (b) Why did nyãya authors prefer to give advan.ced definitions of such complex notions as that of invariable concomitance (vyãpti) with double negatives? It will not be possible to discuss all these problems within the compass of this short article. Only certain aspects of the idea of negation will be dealt with.